2015
DOI: 10.3892/br.2015.417
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and lung cancer risk of patients with type 2 diabetes mellitus: A meta-analysis

Abstract: Objectives: The objective of this study was to evaluate the association between metformin therapy and the incidence of gastric cancer (GC) in patients with type 2 diabetes mellitus (T2DM). Methods: We systemically searched the following databases for studies published between the databases' dates of inception and Nov. 2016: PubMed, Embase, the Cochrane Library, the Web of Science, and the China National Knowledge Infrastructure (CNKI). Hazard ratios (HR) and corresponding 95% confidence intervals (CIs) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…In recent years, a number of retrospective epidemiological and pre-clinical studies have supported the use of metformin as an adjuvant in the chemotherapy for cancer treatment [21]. In lung cancer patients with diabetes, meta-analysis showed that the use of metformin improved survival [22]. A retrospective study from our group showed that in advanced NSCLC patients with type 2 diabetes, metformin together with EGFR-TKI resulted in longer PFS and OS [23].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of retrospective epidemiological and pre-clinical studies have supported the use of metformin as an adjuvant in the chemotherapy for cancer treatment [21]. In lung cancer patients with diabetes, meta-analysis showed that the use of metformin improved survival [22]. A retrospective study from our group showed that in advanced NSCLC patients with type 2 diabetes, metformin together with EGFR-TKI resulted in longer PFS and OS [23].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its widespread use, an abundance of epidemiological data is available for how metformin might influence other disease states. Retrospective studies have found that taking metformin is associated with improved cancer outcomes, with reductions in cancer incidence and with decreased cancer mortality observed across many tumor types (Evans et al, 2005; Gandini et al, 2014; He et al, 2012; Lee et al, 2012; Zhu et al, 2015). These findings have resulted in studies examining the anti-tumorigenic properties of metformin and other biguanides on cancer cell lines and in mouse models of cancer, as well as clinical trials exploring potential roles for metformin in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 DM is considered as a risk factor for many types of cancer (Shlomai et al, 2016;Cignarelli et al, 2018;Sacerdote & Ricceri, 2018). Multiple studies have suggested that metformin use was associated with lower incidences of various solid tumours such as pancreatic, colorectal, gastric, lung and breast cancer (Gandini et al, 2014;Wang et al, 2014;Zhu et al, 2015;Shlomai et al, 2016;Kobiela et al, 2018;Li et al, 2018b). There is also accumulating evidence that supports an association of metformin use with improved outcome of several types of solid tumours (Chu et al, 2018;Hu et al, 2018;Kobiela et al, 2018;Li et al, 2018b;Tang et al, 2018;Xin et al, 2018).…”
mentioning
confidence: 99%